APLIKASI PENDATAAN STOK PUPUK, OBAT-OBATAN, BIBIT DAN ALAT-ALAT PERTANIAN BERBASIS WEB PADA CV.CITRA TANI SUBUR: System, Information, MySQL, Application, Stock, Web. - Wati, Nila; Dharmawan, Bibit; -, Riswan (JURNAL AKADEMIKA, 2024)
CV. Citra Tani Subur is a company engaged in the distributor of goods and services such as providers of plant medicines, fertilizers, seeds, and others. In this company still uses recording goods using a manual system, so it takes a long time and is less accurate. The purpose of this research is to design and build a stock data collection application that is able to process stock data or handle files, the method carried out by the waterfall method. This web-based application was built using the PHP programming language, HTML with MySQL database on XAMPP. The input data needed is incoming goods data, outgoing goods data, stock data, report data. The process carried out is the process of processing stock data, processing incoming goods and outgoing goods, while the output is in the form of incoming goods reports, outgoing goods reports, warehouse goods reports. The result is a web-based application for data collection of stocks, fertilizers, medicines, seeds and agricultural tools. It is suggested that the next researcher can develop this application by designing its profile so that it is android-based.